2012
DOI: 10.1186/1550-2783-9-10
|View full text |Cite
|
Sign up to set email alerts
|

Feed restriction and a diet's caloric value: The influence on the aerobic and anaerobic capacity of rats

Abstract: BackgroundThe influence of feed restriction and different diet's caloric value on the aerobic and anaerobic capacity is unclear in the literature. Thus, the objectives of this study were to determine the possible influences of two diets with different caloric values and the influence of feed restriction on the aerobic (anaerobic threshold: AT) and anaerobic (time to exhaustion: Tlim) variables measured by a lactate minimum test (LM) in rats.MethodsWe used 40 adult Wistar rats. The animals were divided into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Based on an average daily food intake of animals fed with the hypercholesterolemic or normal diets, both untreated and treated with guarana or caffeine, and body weight measurements after 2 months, we observed that the hypercholesterolemic groups intake the least amount of food, but their body weights were not altered when compared with the normal diet groups. This may be due to the higher energy value of the hypercholesterolemic diet when compared with the normal diet (Moura et al, 2012).…”
mentioning
confidence: 99%
“…Based on an average daily food intake of animals fed with the hypercholesterolemic or normal diets, both untreated and treated with guarana or caffeine, and body weight measurements after 2 months, we observed that the hypercholesterolemic groups intake the least amount of food, but their body weights were not altered when compared with the normal diet groups. This may be due to the higher energy value of the hypercholesterolemic diet when compared with the normal diet (Moura et al, 2012).…”
mentioning
confidence: 99%